SULFUR COMPOUNDS OF PHYTOPLANKTON ORIGIN IN THE ATMOSPHERIC BOUNDARY-LAYER - コガ, セイジ; タナカ, ヒロシ; KOGA, Seizi; TANAKA, Hiroshi (National Institute of Polar Research, 1991)
P(論文) A box model was made to understand how dimethylsulfide (DMS or CH_3SCH_3), released from the ocean surface to the atmosphere, contributes to produce background aerosol particles over the open ocean. Dimethylsulfide undergoes a photooxidation reaction with OH radical during the daytime, but with NO_3 radical during nighttime. This reaction has two pathways : hydrogen abstraction and OH addition to the sulfur atom. The oxidation of DMS produces sulfur dioxide (SO_2) and methanesulfonic acid (MSA or CH_3SO_3H) as intermediate products, and non-sea-salt sulfate (nss-SO_4^<2->) as an end product. We considered the reaction processes in detail to obtain quantitatively the concentrations of SO_2,MSA and nss-SO_4^<2->. The calculated concentrations are consistent with the observed values. It is concluded that DMS is a dominant source of aerosol particles included nss-SO_4^<2-> in the marine atmosphere. The calculation indicates that most nss-SO_4^<2-> must be produced by heterogeneous reactions of SO_2 through cloud droplets. Other processes, MSA oxidation and homogeneous SO_2 oxidation, are inefficient in producing abundant nss-SO_4^<2->. departmental bulletin paper